Vpliv vitamina D na avtoimunske bolezni - Kvartuh, Anja (Placebo, 2022)
Vitamin D has an important immunomodulatory function. It impacts the differentiation, activation, and proliferation of inflammatory and immune cells. Vitamin D receptor (VDR) is expressed by many immune cells. Antigen-presenting cells (APC) also express enzyme 1-?-hydroxylase, which converts 25-hydroxyvitamin D (25(OH)D) or calcidiol into active 1,25-hydroxyvitamin D (1,25(OH)2D) or calcitriol. Vitamin D deficiency is associated with numerous autoimmune diseases, including psoriasis, type 1 diabetes (T1D), multiple sclerosis (MS), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE). Several clinical trials aiming to determine how vitamin D affects the development of autoimmune diseases have been conducted, but with variable outcomes. Some of them have indicated that maintaining sufficient vitamin D levels eases symptoms of diseases, slows down courses of diseases, increases the effect of other medications or even prevents the occurrence of diseases. Researchers agree that more randomized and controlled studies with a larger sample size are needed to further confirm the positive effects of vitamin D.
Keywords: autoimmune disease; Avtoimunske bolezni; multipla skleroza; multiple sclerosis; psoriasis; psoriaza; revmatoidni artritis; rheumatoid arthritis; sistemski lupus eritematozus; sladkorna bolezen tipa 1; systemic lupus erythematosus; type 1 diabetes; Vitamin D